The Phenomenon of Religious Intolerance in Indonesia As a Source of Creation in GAMA-A? #2 Dance Works - Rines Onyxi Tampubolon (Institut Seni Indonesia Yogyakarta, 2023)
“GAMA-A? #2” is a work that exists to respond to the realities of life regarding cases of religious intolerance in Indonesia. Cases of religious intolerance are seen as a problem in understanding the essence of the function and meaning of religion. This paper will describe the creative process of forming ideas, concepts, and forms of work originating from the phenomenon of religious intolerance. The creative process begins with reading the problem through the phenomenological method which will help the dance choreographer understand the meaning of various events and human interactions in the phenomenon of religious intelligence in Indonesia. The conclusion of the interpretation of the reality of this problem will be used as the basis for composing a dramatic work which is divided into five scenes by presenting elements from the six religions recognized in Indonesia. The work on the visual form of the work will go through the Alma M. Hawkins Creation Method (Exploration, Improvisation, and Composition) by working on large group dances, with 12 interfaith dancers consisting of six men and six women. The presence of this work aims to answer the problem of cases of religious intolerance in Indonesia to maintain unity in the concept of diversity by creating solidarity based on harmonious humanity. Keywords: Religion, Intolerance, Group Dance Fenomena Intoleransi Agama Di IndonesiaSebagai Sumber Penciptaan dalam Karya Seni Tari GAMA-A? #2Oleh Rines Onyxi Tampubolon, S.Sn, M.SnProgram Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Maritim Raja Ali Haji ABSTRAK“GAMA-A? #2” merupakan karya yang hadir untuk merespon realitas kehidupan tentang kasus intoleransi agama yang ada di Indonesia. Kasus intoleransi agama dipandang sebagai permasalahan dalam pemahaman essensi dari fungsi dan makna agama. Tulisan ini akan menjabarkan proses kreatif pembentukan ide, konsep, dan wujud karya yang bersumber dari fenomena intoleransi agama. Proses kreatif dimulai dengan membaca permasalahan lewat metode fenomenologi yang akan membantu penata tari dalam memahami makna dari berbagai peristiwa dan interaksi manusia dalam fenomena inteloransi agama di Indonesia. Simpulan interpertasi dari realita permasalahan ini yang akan dijadikan landasan dalam menyusun dramatik karya yang dibagi menjadi lima adegan dengan menghadirkan elemen-elemen dari enam agama yang diakui di Indonesia. Penggarapan wujud visual karya akan dilalui dengan Metode Penciptaan Alma M.Hawkins (Eksplorasi, Improvisasi, dan Komposisi) karya garap tari kelompok besar, dengan jumlah penari 12 orangpenari lintas agama yang terdiri dari enam orang laki-laki dan enam orang perempuan. Kehadiran karya ini bertujuan menjawab persoalan kasus intoleransi agama di Indonesia untuk menjaga persatuan dan kesatuan dalam konsepkebinekaan dengan cara menciptakan solidaritas berdasarkan kemanusiaan yang harmonis.Kata Kunci : Agama, Intoleransi, Tari Kelompok